2021
DOI: 10.1097/rti.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Tissue Characterization in Ischemic Cardiomyopathy

Abstract: Ischemic cardiomyopathy (ICM) is one of the most common causes of congestive heart failure. In patients with ICM, tissue characterization with cardiac magnetic resonance imaging (CMR) allows for evaluation of myocardial abnormalities in acute and chronic settings. Myocardial edema, microvascular obstruction (MVO), intracardiac thrombus, intramyocardial hemorrhage, and late gadolinium enhancement of the myocardium are easily depicted using standard CMR sequences. In the acute setting, tissue characterization is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 123 publications
0
24
0
Order By: Relevance
“…Even if excellent collateral circulation develops, symptomatic patients with a CTO usually have a persistent ischemic zone, evidenced by lower fractional flow reserve of the myocardium supplied by a CTO ( 24 ). Cardiac magnetic resonance (CMR) can be used to identify inducible myocardial ischemia and viability in the perfusion territory of the artery with CTO; thus, it is believed that CMR is helpful for selecting patients likely to benefit from revascularization ( 25 ). In a prospective study of 50 consecutive CTO patients undergoing CMR, Bucciarelli-Ducci et al reported that CTO recanalization reduces ischemic burden, favors reverse remodeling, and improves quality of life for patients, showing CMR evidence of significant myocardial inducible perfusion defects and viability ( 26 ).…”
Section: Limited Clinical Benefits Of Percutaneous Coronary Intervent...mentioning
confidence: 99%
“…Even if excellent collateral circulation develops, symptomatic patients with a CTO usually have a persistent ischemic zone, evidenced by lower fractional flow reserve of the myocardium supplied by a CTO ( 24 ). Cardiac magnetic resonance (CMR) can be used to identify inducible myocardial ischemia and viability in the perfusion territory of the artery with CTO; thus, it is believed that CMR is helpful for selecting patients likely to benefit from revascularization ( 25 ). In a prospective study of 50 consecutive CTO patients undergoing CMR, Bucciarelli-Ducci et al reported that CTO recanalization reduces ischemic burden, favors reverse remodeling, and improves quality of life for patients, showing CMR evidence of significant myocardial inducible perfusion defects and viability ( 26 ).…”
Section: Limited Clinical Benefits Of Percutaneous Coronary Intervent...mentioning
confidence: 99%
“…60,61 In order to overcome these limitations, mapping sequences have been developed allowing a more quantitative approach. 51…”
Section: Cine Imagesmentioning
confidence: 99%
“…In particular, there is less influence on image of surface coil, slow intracardiac flow and presence of inflammatory systemic disease. 51 F I G U R E 1 A case of 85-year-old female patient showing acute myocarditis (AM). Trans-thoracic echocardiographic imaging revealed a moderate left ventricular systolic disfunction due to global hypokinesis, more marked in the middle part of anterior and anterolateral wall (arrow A and B), and a mild pericardial effusion in parasternal short axis view (asterisks, A) and apical four chamber view (asterisks, B).…”
Section: T2 Mappingmentioning
confidence: 99%
See 2 more Smart Citations